X-Ray Lithography for Nanofabrication: Is There a Future? - Bharti, Amardeep; Turchet, Alessio; Marmiroli, Benedetta (Frontiers in Nanotechnology, 2022)
X-ray lithography has been first proposed almost 50 years ago, and the related LIGA process around 25 years ago. It is therefore a good time to make an analysis of the technique, with its pros and cons. In this perspective article, we describe X-ray lithography’s latest advancements. First, we report the improvement in the fabrication of the high aspect ratio and high-resolution micro/nanostructures. Then, we present the radiation-assisted synthesis and processing of novel materials for the next generation of functional devices. We finally draw our conclusion on the future prospects of the technique.